Kelengkapan tarich Nabi Muhammad SAW - H. Munawar Chalil (Bulan Bintang, 1966)
ir, Jil 2=c.1-2 ; jil.3 A=c.1-4 ; jil.3 B=c.1-4 ; jil.4 A=c.1-3 ; jil.4 B=c.1-3/ir, jil.1,c.1/why, jil.3 A=c.5/ tr, jil.3 B=c.5/en, jil.3 A=c.6